Evaluating success of an integrated control programme of Hakea sericea Schrader (Proteaceae) in the Western and Eastern Cape Provinces, South Africa through cartographic analysis - Te Roller, Kerry Sharon (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2004.